Pengaruh Konsep Diri Terhadap Kemampuan Pemecahan Masalah Sistem Persamaan Linear Dua Variabel - Andi Puji Widyastuti; Nurul Hikmah; Ratna Yulis Tyaningsih (Pendidikan Matematika FKIP Universitas Mataram, 2026)
Self-concept is one of the psychological factors that can influence students’ problem-solving ability. This study aims to find out the self-concept of grade IX students of SMP Negeri 2 Buer for the 2025/2026 school year, the problem-solving ability of the two-variable linear equation system of grade IX students of SMP Negeri 2 Buer for the 2025/2026 school year, as well as the influence of self-concept on the problem-solving ability of the two-variable linear equation system of grade IX students of SMP Negeri 2 Buer for the 2025/2026 school year. The type of research used is descriptive and ex post facto research. The research population is 56 students in grade IX of SMP Negeri 2 Buer odd semester for the 2025/2026 school year. The sampling technique used is a saturated sampling technique, so the entire population is used as a research sample. The instruments used in this study were self-concept questionnaires and tests of students' problem-solving abilities. The results of the descriptive analysis showed that students' self-concept and overall problem-solving skills were in the medium category. The results of simple linear regression analysis were obtained from the regression equation. . The hypothesis test showed that self-concept had a significant effect on students' problem-solving ability with a contribution of 50.5%. Thus, improving self-concept can be an effective strategy in improving students' problem-solving skills.